Optimization of the blood culture pathway: a template for improved sepsis management and diagnostic antimicrobial stewardship. Issue 3 (March 2018) - Weinbren, M.J.; Collins, M.; Heathcote, R.; Umar, M.; Nisar, M.; Ainger, C.; Masters, P.
Summary: Laboratory processing of blood cultures has remained static over the past 30 years, despite increasing antibiotic resistance and advances in analyser design. At the study hospital, siting the blood culture analyser in the blood sciences laboratory and optimizing the pre-analytical and analytic phases of blood culture management resulted in a reduction in the time taken to detect most blood culture isolates to <12 h. Fifty percent of positive blood cultures containing Escherichia coli were definitively reported with antibiotic susceptibilities in <24 h. More than 85% of blood cultures positive for E. coli had antibiotic susceptibilities reported within 36 h of collection, compared with 66 h at a comparator hospital.